2015
DOI: 10.1093/jxb/erv427
|View full text |Cite
|
Sign up to set email alerts
|

Zeaxanthin-independent energy quenching and alternative electron sinks cause a decoupling of the relationship between the photochemical reflectance index (PRI) and photosynthesis in an evergreen conifer during spring

Abstract: HighlightDecoupling of the photochemical reflectance index and photosynthesis in evergreen conifers during spring is caused by energy-quenching mechanisms that remain undetected by leaf reflectance measurements and remote sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 60 publications
7
33
0
Order By: Relevance
“…Field studies have confirmed that chlorophyll/ carotenoid ratios closely track the seasonal photosynthetic activity of Mediterranean climate evergreen leaves (21,23). This conclusion is further supported by recent spectral and kinetic evidence that demonstrates a close coincidence between seasonal photosynthetic activity, chlorophyll/carotenoid ratios, and spectral reflectance in evergreen conifers (24)(25)(26). Together, these studies suggest that satellite indices of changing pigment levels might provide reliable indicators of evergreen photosynthetic phenology.…”
Section: Significancesupporting
confidence: 65%
See 1 more Smart Citation
“…Field studies have confirmed that chlorophyll/ carotenoid ratios closely track the seasonal photosynthetic activity of Mediterranean climate evergreen leaves (21,23). This conclusion is further supported by recent spectral and kinetic evidence that demonstrates a close coincidence between seasonal photosynthetic activity, chlorophyll/carotenoid ratios, and spectral reflectance in evergreen conifers (24)(25)(26). Together, these studies suggest that satellite indices of changing pigment levels might provide reliable indicators of evergreen photosynthetic phenology.…”
Section: Significancesupporting
confidence: 65%
“…However, over annual time periods, the primary driver of the PRI at leaf and canopy scales is the changing leaf carotenoid pigment pool, typically expressed as the changing ratio of chlorophyll to carotenoid pigments (or its inverse), and not the xanthophyll cycle per se (21)(22)(23)(24)(25). This observation of changing pigment content is particularly relevant for northern evergreen conifers that undergo large seasonal swings in photosynthetic activity and carotenoid pigment levels associated with temperature extremes (24)(25)(26)(27)(28). These findings have led us to reconsider the function of carotenoid pigments in the context of detecting photosynthetic phenology in evergreen conifers.…”
Section: Significancementioning
confidence: 99%
“…The balance between photochemical and carbon assimilation processes ensured by the action of the xanthophyll cycle maintains vegetation in a state optimal for photosynthesis [10]. Extensive studies have been conducted in recent years to explain impairment in the PRI-LUE relationship during spring caused by increased PSI activity upon recovering photosynthesis functions [55,56]. It is furthermore assumed that ATP consumption and cyclic electron flow around PSI help maintain the integrity of chloroplasts in cold environments [57].…”
Section: Use Of Pri For Determining Photosynthetic Parametersmentioning
confidence: 99%
“…Additionally, photoprotective carotenoid pigments accumulate in leaves, especially the xanthophylls, zeaxanthin, and lutein that contribute to nonphotochemical quenching (NPQ) via thermal dissipation of excess light energy (Busch et al, 2007;Verhoeven et al, 2009;Demmig-Adams et al, 2012). Prolonged exposure to low temperature induces sustained nonphotochemical quenching (NPQ S ), where zeaxanthin constitutively dissipates excess light energy (Ensminger et al, 2004;Demmig-Adams et al, 2012;Fréchette et al, 2015).…”
mentioning
confidence: 99%